2011
DOI: 10.5402/2011/529368
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Tuberculosis of Breast: Case Report

Abstract: Tuberculosis of breast is a rare disease which is difficult to differentiate from carcinoma of breast. The involvement of breast can be primary or secondary to some focus in body. A case of secondary tuberculosis of right breast in a 21-year-old female from Kashmir, India, is being reported. Presentation was as a painless discharging sinus of right breast. A tubercular foci of rib was the affecting source of disease. No other evidence of tuberculosis was present in the body. Resection of involved rib segment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…Mammary TB was described in 1829 [7]: A primary involvement occasionally exists [8,9], whereas secondary forms are less uncommon [10]. Considering lung involvement, this patient constitutes a case of secondary breast TB.…”
Section: Discussionmentioning
confidence: 99%
“…Mammary TB was described in 1829 [7]: A primary involvement occasionally exists [8,9], whereas secondary forms are less uncommon [10]. Considering lung involvement, this patient constitutes a case of secondary breast TB.…”
Section: Discussionmentioning
confidence: 99%
“…Presentation of breast tuberculosis is variable. Several studies suggested that though it is a rare disease it should always be suspected when evaluating cases of breast abscesses, fistulae or nodules, with poor response to classical non-tuberculosis antibiotic treatment [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of isolated tuberculosis of the breast ranges from 0.10% to 0.52%. 3 The new classification is: 2 i. Nodulo-caseous tubercular mastitis.…”
Section: Discussionmentioning
confidence: 99%